The structure of the human ABC transporter ABCG2 reveals a novel mechanism for drug extrusion - Narakorn Khunweeraphong (Nature Portfolio, 2017)
Abstract The human ABC transporter ABCG2 (Breast Cancer Resistance Protein, BCRP) is implicated in anticancer resistance, in detoxification across barriers and linked to gout. Here, we generate a novel atomic model of ABCG2 using the crystal structure of ABCG5/G8. Extensive mutagenesis verifies the structure, disclosing hitherto unrecognized essential residues and domains in the homodimeric ABCG2 transporter. The elbow helix, the first intracellular loop (ICL1) and the nucleotide-binding domain (NBD) constitute pivotal elements of the architecture building the transmission interface that borders a central cavity which acts as a drug trap. The transmission interface is stabilized by salt-bridge interactions between the elbow helix and ICL1, as well as within ICL1, which is essential to control the conformational switch of ABCG2 to the outward-open drug-releasing conformation. Importantly, we propose that ICL1 operates like a molecular spring that holds the NBD dimer close to the membrane, thereby enabling efficient coupling of ATP hydrolysis during the catalytic cycle. These novel mechanistic data open new opportunities to therapeutically target ABCG2 in the context of related diseases.